Eurypterids from the Price Formation of Virginia: First Eurypterids from the Mississippian of North America. (January 2023) - Plotnick, Roy E.; Lamsdell, James C.
Abstract: A new hibbertopterid eurypterid, Cyrtoctenus bambachi n. sp., is described from the Early Mississippian (Tournaisian) Price Formation of western Virginia. The same unit yields an unidentifiable stylonurine eurypterid. These are the first eurypterids documented from the Mississippian of North America, and only the fourth locality of this age anywhere in the world to yield eurypterids. UUID: http://zoobank.org/5c84d3a2-ea5a-402c-970d-9b0d867f52c7